2019
DOI: 10.1111/1467-6427.12269
|View full text |Cite
|
Sign up to set email alerts
|

Conversation analysis and family therapy: a narrative review

Abstract: Conversation analysis (CA) can provide insight into interactional micro‐processes of family therapy. Past reviews of CA and family therapy have focused on methodology without descriptions of research findings, reducing the likelihood that the findings of CA research are employed to guide practice. This narrative review provides therapists with a description of CA findings that can inform family therapy practice. Systematic searches of databases, individual journals, and citation analyses were completed in Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…To date, not many formal syntheses of research have focused on in‐session dialogue. The few exceptions include a study on solution‐focused brief therapy process (Franklin et al, 2017) and a narrative review of findings of CA studies of family therapy, but these studies do not attend to change process (Ong, Barnes, & Buus, 2019). Two methodological reviews (Ong, Barnes, & Buus, 2020; Tseliou, 2013) reported the use of CA/DA to examine in‐session dialogue, again without focusing on change process.…”
mentioning
confidence: 99%
“…To date, not many formal syntheses of research have focused on in‐session dialogue. The few exceptions include a study on solution‐focused brief therapy process (Franklin et al, 2017) and a narrative review of findings of CA studies of family therapy, but these studies do not attend to change process (Ong, Barnes, & Buus, 2019). Two methodological reviews (Ong, Barnes, & Buus, 2020; Tseliou, 2013) reported the use of CA/DA to examine in‐session dialogue, again without focusing on change process.…”
mentioning
confidence: 99%
“…There has been scant empirical investigation of how therapists actually manage these potential conflicts in real‐life therapy sessions. One research technique that can reveal how such family conversations are actually conducted is conversation analysis (Ong, Barnes, & Buus, 2019, 2020; Schriver, Buus, & Rossen, 2019; Tseliou, 2013).…”
mentioning
confidence: 99%
“…Put another way, CA seeks to describe how people achieve various social actions through conversation and the methods they employ to achieve them. CA has been applied to different aspects of family therapy (Ong et al, 2019, 2020; Tseliou, 2013). For the current study, two features of conversation are particularly relevant: stance (Du Bois, 2007) and deontics (Stevanovic, 2018; Stevanovic & Peräkylä, 2012, 2014).…”
mentioning
confidence: 99%
“…Through a detailed scrutiny of how people actually talk (e.g., choice of words, prosody, intonation, voice quality, and sequences of talk), CA can reveal how participants in everyday conversations create meaning as a shared accomplishment (Sidnell, 2010). Over the past decades, scholars have applied CA to various institutional settings such as doctorpatient interactions (Heritage & Maynard, 2006), psychotherapy (Ong, Barnes & Buus, 2019;Ong, Barnes & Buus, 2020;Tseliou, 2013), and other helping professions (Graf & Pawelczyk, 2014). Therapy is based on talk, and studying therapeutic talk can produce new insights into therapeutic practice (Parker & O'Reilly, 2013).…”
mentioning
confidence: 99%
“…It unfolds the psychotherapeutic sessions utterance‐by‐utterance and explicates the practices and interactional patterns through which the therapeutic work is carried out” (p. 219). CA can therefore offer insights into the microprocesses occurring in family therapy sessions (Ong et al, 2020; Tseliou, 2013), such as open dialogue network meetings.…”
mentioning
confidence: 99%